Pancreatic Stellate Cells Facilitate Perineural Invasion of Pancreatic Cancer via HGF/c-Met Pathway - Nan, Ligang (Cell Transplant, 2019)
Pancreatic cancer (PC) is a highly lethal cancer that has a strong ability for invasion and metastasis, poor prognosis, and a stubbornly high death rate due to late diagnosis and early metastasis. Therefore, a better understanding of the mechanisms of metastasis should provide novel opportunities for therapeutic purposes. As a route of metastasis in PC, perineural invasion (PNI) occurs frequently; however, the molecular mechanism of PNI is still poorly understood. In this study, we show that the hepatocyte growth factor (HGF)/c-Met pathway plays a vital role in the PNI of PC. We found that HGF promotes PC cell migration and invasion by activating the HGF/c-Met pathway, and enhances the expression of nerve growth factor (NGF) and matrix metalloproteinase-9 (MMP9) in vitro. Furthermore, HGF significantly increased PC cell invasion of the dorsal root ganglia (DRG) and promoted the outgrowth of DRG in cocultured models of PC cells and DRG. In contrast, the capacity for invasion and the phenomenon of PNI in PC cells were reduced when the HGF/c-Met pathway was blocked by siRNA. In conclusion, PSCs facilitate PC cell PNI via the HGF/c-Met pathway. Targeting the HGF/c-Met signaling pathway could be a promising therapeutic strategy for PC.